Flour Industry in Duitama-Boyacá 1920-1940 - Plazas Díaz, Leidy Carolina (Sociedad y Economía, 2012)
The following article is the product of a qualitative research with historical focus on the consolidation of the flour industry in Duitama, based on the review of sources of archive and fieldwork. This text aims to make an historical analysis of the technification in the production of flour and the social changes generated by the arrival of the first factory in the municipality of Duitama, during the period from 1911 to 1940. It also seeks to contribute to the regional studies of the industrial history of the first decades of the 20th century.